Collection development and collection evaluation : - Gabriel, Michael R. (Scarecrow Press, 1995)
Content include: collection development comprehensive bibliography on collection development; collection evaluation comprehensive bibliography on collection evaluation; comprehensive bibliography on acquisitions; examples of collection development policies; national guidelines and standards regarding collection development and collection evaluation; glossary of terms associated with collection development and library telecommunications for networking anf resource sharing.